2022
DOI: 10.3390/foods12010158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Slaughter Age of Holstein Friesian Bulls on Meat Quality: Chemical Composition, Textural Characteristics, Sensory Attributes and Fatty Acid Profile

Abstract: This study aimed to investigate the effects of slaughter age (young vs. old), muscle type (Longissimus dorsi (LD), Gluteus medius (GM)) and fat deposits (kidney knob and channel fat, subcutaneous fat, intramuscular fat) on chemical, organoleptic, textural characteristics and fatty acid composition of Holstein Friesian bull meat. For this purpose, the carcasses of 26 Holstein Friesian bulls that had been fattened on the same private farm were assigned to two experimental groups based on their age at slaughter: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…These results are consistent with data from studies A. Diler et al (2022). The researchers also found that the shade of muscle tissue in cattle is not a source of variability in their chemical composition.…”
Section: Resultssupporting
confidence: 89%
“…These results are consistent with data from studies A. Diler et al (2022). The researchers also found that the shade of muscle tissue in cattle is not a source of variability in their chemical composition.…”
Section: Resultssupporting
confidence: 89%
“…According to previous findings, surface visual traits (marbling) are significantly influenced by breeding methods [ 48 ]. The examined breeds, Boran, Senga, and Sheko, have very little marbling (sirloin: 4.56 ± 1.60, chuck: 3.82 ± 1.06, sirloin: 3.03 ± 0.68, chuck: 2.73 ± 0.90, and sirloin: 2.88 ± 1.42, chuck: 2.92 ± 1.67), and there were no differences in marbling means ( p < 0.01) between the various cattle types.…”
Section: Resultsmentioning
confidence: 99%
“…The crude fat content positively influences the juiciness of the meat as intramuscular fat, but not as cover fat around the meat [ 40 , 41 ]. Additionally, Diler et al [ 42 ] reported that muscle and fat type are essential sources of variations in the textural characteristics, sensory panel attributes, and fatty acid profile of meat from Holstein-Friesian bulls. The highest collagen content was found in PHF—in culinary beef production, this indicator should be as low as possible due to its negative effect on meat tenderness [ 43 ].…”
Section: Discussionmentioning
confidence: 99%